Comparison of Meteorin-like Protein Infusion and Moderate-Intensity Exercise on Cardiac Mast Cell and Plasma Cell Dynamics and Musclin Levels in Female Rats - Ertuğrul, Nazife Ülker; Gökdere, Ebru; Keskin, Feyza; Delice, Nurcan; Ertuğrul, Tuğrul; Sevilgen, Gökçen; Canpolat, Sinan (Turkish Society of Cardiology, 2025)
Objective: Moderate-intensity exercise modulates the immunological response in cardiac tissue. Meteorin-like protein (METRNL) is a myokine secreted by muscle cells during exercise and is involved in immune response regulation. However, the effects of metrnl on mast cells and plasma cells in cardiac tissue are not fully understood. This study was designed to assess the effects of exogenous metrnl infusion on the cardiac mast cells and plasma cells. In addition, serum levels of musclin, an exercise-responsive factor, were evaluated during the effects of moderate-intensity exercise on cardiac immune cells. Method: Twenty-seven female rats were randomly divided into three groups (n = 9 each): control (deionized water), exercise (moderate-intensity swimming exercise) and metrnl (1 µg/day). For histological studies, hematoxylin-eosin, toluidine blue and methyl green-pyronin staining were performed on heart tissues. Musclin levels were measured in serum samples using the ELISA method. Results: Metrnl infusion increased cardiac mast cell and plasma cell numbers in female rats like moderate-intensity exercise. In addition, the increase in cardiac mast cell count was greater in the exercise group, whereas musclin concentration decreased in female rats subjected to moderate-intensity exercise. Conclusion: Our data suggest that moderate-intensity exercise's effects on the cardiac immune system may be mediated by musclin downregulation and metrnl-dependent upregulation of cardiac mast cells and plasma cells. Thus, exercise-induced metrnl may affect the cardiac immune response by modulating cardiac immune cells. © Available online at archivestsc.com.Content of this journal is licensed under a Creative Commons Attribution NonCommercial-NoDerivatives 4.0 International License.
Dişi Sıçanlarda Kardiyak Mast Hücre ve Plazma Hücre Dinamikleri ve Musklin Seviyeleri Üzerinde Meteorin-Like Protein İnfüzyonu ile Orta Şiddetli Egzersizin Karşılaştırılması
Keywords: Exercise; heart; mast cell; meteorin-like protein; musclin (osteocrin); plasma cell